2018
DOI: 10.15408/sjie.v7i1.6074
|View full text |Cite
|
Sign up to set email alerts
|

Mergers and Acquisitions in Selected Frontier Markets of Asia

Abstract: This paper aims to provide contemporary and comparative information on mergers and acquisition activities. The findings have shown that Vietnam is very active in mergers and acquisitions activities, for instance in Vietnam 2946 transactions were announced, and 2114 completed in the last decade. Furthermore, Vietnam has a distinctive element of merging local firms; Out of top 20 deals, in 18 transactions target firms and acquirer both were from Vietnam. On the other hand, Sri Lanka has the highest percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…From the analysis, it has been observed that no profitability has increased and no leverage has reduced from merger and acquisition. These results are in consistent with the results of Rashid & Naeem, (2017) and Ahmed et al, (2018) which says that there is no significant impact on firm's profitability after M&As in case of Pakistan banking sector.…”
Section: Discussionsupporting
confidence: 90%
“…From the analysis, it has been observed that no profitability has increased and no leverage has reduced from merger and acquisition. These results are in consistent with the results of Rashid & Naeem, (2017) and Ahmed et al, (2018) which says that there is no significant impact on firm's profitability after M&As in case of Pakistan banking sector.…”
Section: Discussionsupporting
confidence: 90%
“…The degree of protection that investors receive in various jurisdictions depends on the characteristics of the legal rules themselves and the quality of legal enforcement (Kothari et al 2012;La Porta et al 1997). Due to their weak legal and enforcement environment around shareholders' interests, emerging and frontier markets may not sufficiently protect shareholders' interests (Ahmed et al 2018;Ma et al 2009). In a separate legal enforcement study, La Porta et al (2002) and note that countries governed by civil laws provide investors with weaker legal rights, 5 as civil law tends to be associated with lower financial development levels.…”
Section: Legal Enforcementmentioning
confidence: 99%
“…Besides merger, the other strategy such as acquisition of Islamic business units of full-fledged Islamic banks also can be do. Ahmed, Ahmed, & Kanwal (2018) said that the merger and acquisition activity will increase the performance of the companies in the market. But, the merger in the market could deteriorate the competitive process (Ahamed, 2012).…”
Section: Resultsmentioning
confidence: 99%